THE PROBLEMS IN THE COMPREHENSIVE ESTIMATION OF THE INTELLECTUAL CAPITAL OF ENTERPRISES - Чуприн, К. С.; Чуприна, О. А. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
In the paper the basic problems in the estimation of the intellectual capital of enterprises its components are considered; the experience is generalized and a critical analysis of the methodological approaches of this estimation is conducted; the expediency of complex using of different methods of the intellectual capital estimation and the necessity of theirs adaptation to the peculiarities of every particular company are proved.